Using the prototype willingness model to predict doping in sport. Issue 5 (31st October 2013) - Whitaker, L.; Long, J.; Petróczi, A.; Backhouse, S. H.
<x xml:space="preserve">Abstract</x> To enable preventive measures to be designed, it is important to identify modifiable distal and proximal factors underlying doping behavior. This study investigated aspects of the prototype willingness model in relation to doping. A cross‐sectional study was conducted involving 729 competitive athletes. Following ethical approval, athletes (mean age = 28.8 ± 10.1 years; 63% male) completed an online questionnaire, which assessed doping‐related attitudes, norms, prototype perceptions, outcome expectancies, and behavioral willingness. Using hierarchical multiple regression analysis, 54.4% of the total variance in willingness to dope was explained. Specifically, past doping, attitudes, and favorability of performance enhancing substance user prototypes were the strongest unique predictors of willingness to dope. Athletes appeared most willing to dope if they were to suffer an injury, a dip in performance, or think others are doping and getting away with it. National‐level athletes displayed significantly greater willingness to dope (Kruskal‐Wallis γ2 = 35.9, P < 0.001) and perceived themselves as significantly more similar to a doper (Kruskal‐Wallis γ2 = 13.4, P = 0.004) than athletes competing at any other level. The findings highlight the importance of extending anti‐doping provision beyond elite‐level sport and the need to target athletes' doping‐related perceptions.